Pengaruh Minat Masyarakat Terhadap Produk British Propolis - Sri Laksmi Pardanawati; Fandy Tri Apriyono (ITB AAS INDONESIA, 2021)
This study aims to determine what factors influence consumer purchase interest in British propolis products among students and lecturers of ITB AAS Surakarta. The variable consists of 4 independent variables (independent), namely product information, prices, promotions and business opportunities. This study uses a quantitative approach with data collection methods carried out through instruments or questionnaires distributed online to students and lecturers of ITB AAS Surakarta. The samples taken were as many as 92 respondents with the system. The data obtained were then processed using the SPSS version 23 application. This analysis used the validity test, reliability test, multiple linear regression test, statistical test through the T test, F count and the coefficient of determination (R2). The results of the t test show that product information has a significant effect on purchase intention, while price, promotion and business opportunities partially do not have a significant effect on consumer buying interest. The results of the F-test show that product information, prices, promotions and business opportunities simultaneously have a significant effect on consumer buying interest. While the R2 test results show that product information, prices, promotions and business opportunities significantly influence consumer buying interest with an effect of 39.8%. While the remaining 60.2% is influenced by other variables outside this model. Keywords: Product, Price, Promotion, Business Opportunities, Consumer Purchase Interest